Evolution Type Inverse Problem for Reaction - Diffusion - Convection System: Exploring Patterns in Chemically Reacting Systems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Inverse problems related with the convection-diffusion equation are of much scientific significance, as they show up in the demonstrating of numerous practical problems. The investigation of spatiotemporal patterns in chemically reacting systems is an intriguing subject which has pulled in significant enthusiasm in the course of recent years.